Implementasi Corporate Social Responsibility Dan Dampaknya Terhadap Kinerja Keuangan - Putri, Putu Claudia Tamara; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p16, 2019)
The purpose of this research is to find out the form of CSR implementation implemented by the St. Regis Bali Resort and to find out the impact of implementing CSR on hotel financial performance. The type of data used is qualitative data, with primary and secondary data sources. Primary data in the form of interviews, and secondary data in the form of hotel financial statements for several periods before and after conducting CSR. The technique of collecting data is by interview, observation, and documentation. The results of the study show the hotel The St. Regis Bali Resort applies several forms of CSR, namely (1) social sector, (2) environmental field. CSR has a positive impact on financial performance, seen from the increase in the number of sales. Increasing the number of sales, it will affect sales and income which will affect the level of profit. Keywords : Corporate social responsibility, financial performance, CSR.